ANALYZING THE RELATION BETWEEN EMPLOYEE ENGAGEMENT AND EMPLOYEE PERFORMANCE AT HOTEL GRAN PURI MANADO - Tanto, Hendra Wijaya; Lambey, Linda .; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: This research is qualitative analysis interview, the population are the employees who has worked for a long period in Hotel Gran Puri Manado, and the sample using snowball sampling. The variables used in this research were taken from the literature to determine the relation between employee engagement and employee performance. The data were gathered through interview with the informants. The result showed that the employees are engaged with the company and showed a positive bond with the company which results in their vision to contribute to the company, to improve it and feeling the sense of returning the favor to the company. The conclusion that can be drawn from this research are employee engagement is very important for every organization because it could increase employee performance and productivity, the employees in Hotel Gran Puri Manado have shown that they have a motivation in doing their job. This research recommends Hotel Gran Puri Manado should provide a clear career path for every employee without differentitate each employee and always keep examining the employee who have worked extra hard when giving a bonus.Â Keywords: employee engagement, employee performance